2017
DOI: 10.9734/bjmmr/2017/33648
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital Use of Oral Rehydration Therapy and Zinc and the Risk of Dehydration in Childhood Diarrhoea

Abstract: Background: Diarrhoea is a leading cause of childhood mortality globally. The use of oral rehydration therapy (ORT) with zinc supplementation is recommended in the treatment of childhood diarrhoea. Objective: To determine the pattern of pre-hospital use of ORT and zinc among children with diarrhoea at the secondary levels of health care in Nigeria. Methods: A cross-sectional survey was conducted over a six-month period at two secondary health facilities among children with diarrhoea. A structured questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Based on this, the study showed that 39.6% (35.6%-43.9%) of the studied participants' households had used zinc bundled with ORS at least once in the last 12 months. This finding was higher than the study findings Open access from different corners of the world, as in Nigeria, 8.3% 21 ; in Sudan, where only 18.9% and 14.8% of the children had received ORS and zinc supplements, respectively 22 ; and in Ethiopia, where the EDHS 2016 reported that 17% of them received a combination of zinc and ORS. 7 The discrepancy might be due to sociocultural differences, study area differences and the time of study considered for those of the studies and surveys conducted even in the study area.…”
Section: Discussioncontrasting
confidence: 71%
“…Based on this, the study showed that 39.6% (35.6%-43.9%) of the studied participants' households had used zinc bundled with ORS at least once in the last 12 months. This finding was higher than the study findings Open access from different corners of the world, as in Nigeria, 8.3% 21 ; in Sudan, where only 18.9% and 14.8% of the children had received ORS and zinc supplements, respectively 22 ; and in Ethiopia, where the EDHS 2016 reported that 17% of them received a combination of zinc and ORS. 7 The discrepancy might be due to sociocultural differences, study area differences and the time of study considered for those of the studies and surveys conducted even in the study area.…”
Section: Discussioncontrasting
confidence: 71%
“…Oral zinc therapy could help reduce the severity and duration of diarrhoea in children above six months but may not have significant effect in children under six months of age (Lazzerini and Wanzira, 2016). Besides, Zinc absorption during diarrhoea may be reduced and vomiting may be a possible side effect (Ogunlesi et al, 2017;Somji et al, 2019). In Bangladesh, a combination of ORS, zinc and vitamin A supplementation was very effective at reducing death in children caused by diarrhoea (Billah et al, 2019).…”
Section: Treatment and Management Of Diarrhoeal Diseasesmentioning
confidence: 99%
“…This finding was higher than in other parts of the world, such as Nigeria (8.3%) 18 , among the 15 highest-burden countries where ORS and zinc coverage levels were accounted for as 2% or less, 9 Sudan, where 18.9% and 14.8% of them had received ORS and zinc, respectively; 19 and Ethiopia, where the 2016 EDHS reported that 17% had received a combination of zinc and ORS. 12 The variation could be due to socio-cultural and geographical differences, as well as the time frame for the studies and surveys conducted even within the study area.…”
Section: Discussionmentioning
confidence: 66%